Comparison of Fatty Acid Composition of Some Tissues and Conversion Ratios of Stomach Containing Fatty Acids to Tissue Fatty Acids in Barbus capito capito Gldenstaed, 1773 - ARAS, N.M.; HASILOGLU, M.A.; HALILOGLU, H.I.; BAYIR, A.; SIRKECIOGLU, A.N. (Asian Journal of Chemistry, 2010)
In this study, it was aimed to investigate the conversion ratios of stomach containing fatty acids to fatty acid profiles of muscle, gonad, gill, liver and adipose tissues and gastric contents in Barbus capito capito Güldenstaed, 1773. The significant differences were determined between gastric contents and adipose and gonad tissues in terms of total saturated fatty acids (SFA), similar saturated fatty acids values were found in the other tissues. The highest monounsaturated fatty acid (MUFA) amounts were found in adipose tissue. n-3 Polyunsaturated fatty acid (n-3 PUFA) and n-6 polyunsaturated fatty acid levels of muscle, gonad, gill and liver were higher than diet's n-3 and n-6 polyunsaturated fatty acids. However, n-3/n-6 polyunsaturated fatty acid ratio significantly increased in all tissues except adipose. Palmitic acid in total saturated fatty acids and oleic acid in total monounsaturated fatty acid were determined as the most abundant fatty acids. Total saturated fatty acids in the diet (26.95±1.68 %) augmented to 34.30 ± 2.57 % in gonad and decreased to 20.15±2.2 % in adipose tissue. Although monounsaturated fatty acid amounts in diet (35.82 ± 2.48 % decreased to 26.66 ± 2.48 %) in muscle, n-3 polyunsaturated fatty acid amount of diet (5.37 ± 2.04 %) increased to 24.2±1.89 % in muscle.